The Multivariate Müntz-Szasz Problem in Weighted Banach Space on Rn - Xiangdong Yang (Abstract and Applied Analysis)
The purpose of this paper is to give an extension of Müntz-Szasz theorems to multivariable weighted Banach space. Denote by {λk=(λk1,λk2,...,λkn)}k=1∞ a sequence of real numbers in R+n. The completeness of monomials {tλk} in Cα is investigated, where Cα is the weighted Banach spaces which consist of complex continuous functions f defined on Rn with f(t) exp(-α(t)) vanishing at infinity in the uniform norm.